Co-infection with Legionella and SARS-CoV-2: a case report - Masaru Shimizu; Yusuke Chihara; Sakiko Satake; Astuko Yone; Mari Makio; Hideki Kitou; Tomohiro Takeda (JA Clinical Reports, 2021)
Abstract Introduction We report a case of COVID-19 with Legionella co-infection that was treated successfully. Case report A 73-year-old man presented to the hospital with symptoms of fatigue that continued for the next 5 days. The patient was receiving docetaxel and prednisolone chemotherapy for prostate cancer. Laboratory findings on admission showed positive urine Legionella antigen test and SARS-CoV-2 test. He was administered antiviral and antibacterial agents, and a corticosteroid. Pneumonia exacerbated on day 2 of hospitalization. The patient underwent tracheal intubation and began receiving multidisciplinary care. On day 8 of hospitalization, his oxygenation improved, and the patient was extubated. He discharged on day 27 of hospitalization. Conclusions The patient had a favorable outcome with early diagnosis and early treatment of both diseases. Patients with severe COVID-19 disease need to be evaluated for co-infection. Further, early diagnosis and early treatment of the microbial bacteria causing the co-infection are important.